A multi-modal energy harvesting device for low-frequency vibrations - Ramírez, J.M. (2018)
This paper presents an innovative design of a low-frequency multi-modal system vibration-based energy harvester (VEH) for powering wireless autonomous monitoring systems wind turbines of 30 kW. The main objective is to design an energy harvesting device capable to operate in a very low-frequency bandwidth (3 to 10 Hz) increasing as much as possible the operational bandwidth by enhancing the amplitude of the second mode of vibration. The electrical power performance is evaluated for four different energy harvesting designs, which are mainly composed of multi-beams cantilevers with tip masses. For the harvesting system with two multiple-beams trident, a rigid beam is selected to join them. This versatile geometric configuration offers the possibility to modify the vibration characteristics of the harvester in several alternative ways, not only by increasing the tip mass which may be not favorable from a structural viewpoint. The resonant frequencies values, the time voltage signals and the electric power are obtained through a finite element beam formulation early proposed by the authors, capable to modeling three dimensional systems. The numerical results are validated through experimental tests. Regarding the output power, the most promising design with two multiple-beams trident with a tip mass delivers 36.48 μW and 96.04 μW in the proposed range of operation (first two resonance frequencies 4.76 and 7.91 Hz, respectively) excited by 0.1 g of base acceleration. This clearly indicates that the device is a very good candidate for the proposed application of autonomous wireless monitoring, since the output power is larger than the minimum of 20 μW required.